Asymptotics of eigenvalues of regular Sturm-Liouville problems with eigenvalue parameter in the boundary condition for integrable potential - Coskun, Haskiz; Baskaya, Elif (MATHEMATICA SCANDINAVICA, 2010)
In this paper we obtain asymptotic estimates of eigenvalues for regular Sturm-Liouville problems having the eigenparameter in the boundary condition without smoothness conditions on $q$.